Production of biofilm by Listeria monocytogenes in different materials and temperatures - Bonsaglia, E. C R [UNESP]; Silva, N. C C [UNESP]; Fernades Júnior, A. [UNESP]; Araújo Júnior, J. P. [UNESP]; Tsunemi, M. H. [UNESP]; Rall, V. L M [UNESP] (Elsevier, 2014)
Listeria monocytogenes, considered as one of the most important foodborne pathogens, is easily found on surfaces, particularly in the form of a biofilm. Biofilms are aggregates of cells that facilitate the persistence of these pathogens in food processing environments conferring resistance to the processes of cleaning and may cause contamination of food during processing, thus, representing a danger to public health. Little is known about the dynamics of the formation and regulation of biofilm production in L.monocytogenes, but several authors reported that the luxS gene may be a precursor in this process. In addition, the product of the inlA gene is responsible for facilitating the entry of the microorganism into epithelial cells that express the receptor E-cadherin, also participates in surface attachment. Thus, 32 strains of L.monocytogenes isolated from different foods (milk and vegetables) and from food processing environments were analyzed for the presence of these genes and their ability to form biofilms on three different surfaces often used in the food industry and retail (polystyrene, glass and stainless steel) at different temperatures (4, 20 and 30°C). All strains had the ilnA gene and 25 out of 32 strains (78.1%) were positive for the presence of the luxS gene, but all strains produced biofilm in at least one of the temperatures and materials tested. This suggests that genes in addition to luxS may participate in this process, but were not the decisive factors for biofilm formation. The bacteria adhered better to hydrophilic surfaces (stainless steel and glass) than to hydrophobic ones (polystyrene), since at 20°C for 24h, 30 (93.8%) and 26 (81.3%) produced biofilm in stainless steel and glass, respectively, and just 2 (6.2%) in polystyrene. The incubation time seemed to be an important factor in the process of biofilm formation, mainly at 35°C for 48h, because the results showed a decrease from 30 (93.8%) to 20 (62.5%) and from 27 (84.4%) to 12 (37.5%), on stainless steel and glass, respectively, although this was not significant (. p=0.3847). We conclude that L.monocytogenes is capable of forming biofilm on different surfaces independent of temperature, but the surface composition may be important factor for a faster development of biofilm. © 2013 Elsevier Ltd.
Keywords: Biofilm; Listeria monocytogenes; LuxS; Temperatures